2023
DOI: 10.1128/spectrum.05241-22
|View full text |Cite
|
Sign up to set email alerts
|

OmpC-Dependent Bile Tolerance Contributes to E. coli Colonization of the Mammalian Intestine

Abstract: Every mammalian intestine is colonized with Escherichia coli . Although E. coli is one of the most studied model organisms, how it colonizes the intestine is not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Remarkably, closer inspection of the genes flanking the intergenic sequences represented in the concatenated targets revealed that certain functions were over-represented amongst the identified ITGR targets. Indeed, aside from the rcsDB locus, which acts as a master regulator for capsule biosynthesis ( 41 ), most of the flanking genes were involved primarily in antibiotic resistance, including: (i) yedS, within the previously identified yedR–yedS locus, which appears to mediate resistance against carbapenems ( 42 ); (ii) emrKY, within the emrKY–evgAS locus, which encodes for an efflux system that appears to be activate in response to tetracycline ( 43 ); (iii) evgAS , within the emrKY–evgAS locus, which encodes for a two-component regulatory system that controls the expression of several antibiotic resistance genes in E. coli ( 44 ); (iv) mdtABCD and baeSR , within the ibsB–(mdtABCD-baeSR ) locus, which appears to encode for a multidrug efflux pump and its corresponding two-component regulatory system, respectively ( 45 ); and (v) ompC , within the ompC–rcsDB locus, which encodes for an outer membrane porin implicated in resistance to various antibiotics ( 46 ) as well as bile salts required for successful colonization of the mammalian gut ( 47 ). Interestingly, these findings seem to mirror previous analyses that have identified ITGRs associated with antibiotic resistance genes as particularly informative for human and bovine E. coli strains ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, closer inspection of the genes flanking the intergenic sequences represented in the concatenated targets revealed that certain functions were over-represented amongst the identified ITGR targets. Indeed, aside from the rcsDB locus, which acts as a master regulator for capsule biosynthesis ( 41 ), most of the flanking genes were involved primarily in antibiotic resistance, including: (i) yedS, within the previously identified yedR–yedS locus, which appears to mediate resistance against carbapenems ( 42 ); (ii) emrKY, within the emrKY–evgAS locus, which encodes for an efflux system that appears to be activate in response to tetracycline ( 43 ); (iii) evgAS , within the emrKY–evgAS locus, which encodes for a two-component regulatory system that controls the expression of several antibiotic resistance genes in E. coli ( 44 ); (iv) mdtABCD and baeSR , within the ibsB–(mdtABCD-baeSR ) locus, which appears to encode for a multidrug efflux pump and its corresponding two-component regulatory system, respectively ( 45 ); and (v) ompC , within the ompC–rcsDB locus, which encodes for an outer membrane porin implicated in resistance to various antibiotics ( 46 ) as well as bile salts required for successful colonization of the mammalian gut ( 47 ). Interestingly, these findings seem to mirror previous analyses that have identified ITGRs associated with antibiotic resistance genes as particularly informative for human and bovine E. coli strains ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse colonization experiments were performed as described previously ( 49 , 73 , 76 79 ). Briefly, at least two sets of three CD-1 male mice (Charles River Laboratories, Wilmington, MA), aged 6–8 weeks, were acclimatized for 5 days, then transferred to individual cages and provided water containing streptomycin sulfate (5 g/L) for 24 h. Streptomycin sulfate selectively eliminates resident facultative anaerobes, which opens a niche for introduced E. coli .…”
Section: Methodsmentioning
confidence: 99%
“…Streptomycin-treated mice were colonized separately with E. coli MG1655 Str R Nal R wild type or E. coli MG1655 Str R ∆ glnG::cam , and on day 9 of colonization, when the mice were stably colonized, the mice were euthanized and total RNA was extracted from cecal mucus as previously described ( 79 ). Briefly, the cecal contents were squeezed out, and the lumen of the ceca was rinsed with Hanks salt solution (Thermo Scientific, catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation